Aesthetic analysis of the title in Persian novels (1953 – 1978) - Sanaz Khoshhesab; Soussan Jabri; Mousa Parnian (مطالعات زبانی و بلاغی)
Title is one of the main pillars in a literary work, a base which, if chosen correctly and thoughtfully, will have a significant impact on attracting the audience. This is certainly more prominent in fiction; the proper choice of title from an aesthetic and literary point of view, can highlight the coherent structure of a work of fiction. However, such studies have not been conducted comprehensively on the titles of Persian stories. In this article, based on library sources, the aesthetic function of the titles of 60 Persian novels written between the years 1953 to 1978 are examined and analyzed concerning grammatical superstructure, sounds, words, music and imagery. The research results show that, since the combination and collocation of words has a more effective role in the association of emotions and the meaning; most of the titles have been selected in combination which are either additional or joined with the preposition and. In the titles, phonemic combinations of the letters produce musical rhythms that seem to have been created by the authors to induce specific meanings. Alliteration and repetition, among figures of speech,  and   congeries and allusion, among figures of thought, have been used more often. Furthermore, the use of metonymy and metaphor is more prominent than other devices.